1982
DOI: 10.1677/joe.0.0920195
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Immunological Properties of Different Molecular Species of Human Follicle-Stimulating Hormone: Electrofocusing Profiles of Eight Highly Purified Preparations

Abstract: Eight highly purified human pituitary FSH preparations and purified preparations of the α-and β-subunits of FSH were fractionated by an electrofocusing technique in the pH range of 2·5–10·0 on a sucrose density gradient. The human (h) FSH activity in each of the eluted fractions was monitored by an in-vitro bioassay and a radioimmunoassay procedure. After electrofocusing, the overall recovery of the biological activity of the eight preparations was between 80 and 94% (mean 88%). On the other hand, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 0 publications
1
12
1
Order By: Relevance
“…In previous reports from our laboratory, rat pituitary luteinizing hormone (LH) separated into 7 isoelectric components which had different ratios of in vitro biological activity to immunoreactivity (B: I), suggesting that the discrepancy between the bioassay and immunoassay of glycoprotein hormones is mainly responsible for the electrical heterogeneity (Wakabayashi, 1977(Wakabayashi, , 1980Hattori et al, 1983). Similar studies on human gonadotropins were reported by Diczfalusy and coworkers Van Damme et al, 1977;Zaidi et al, 1982a, b). Avian LH also consists of several components in the pituitary glands of chicken, Japanese quail, guinea fowl and duck (Hattori and Wakabayashi, 1979;Wakabayashi, 1980).…”
mentioning
confidence: 56%
“…In previous reports from our laboratory, rat pituitary luteinizing hormone (LH) separated into 7 isoelectric components which had different ratios of in vitro biological activity to immunoreactivity (B: I), suggesting that the discrepancy between the bioassay and immunoassay of glycoprotein hormones is mainly responsible for the electrical heterogeneity (Wakabayashi, 1977(Wakabayashi, , 1980Hattori et al, 1983). Similar studies on human gonadotropins were reported by Diczfalusy and coworkers Van Damme et al, 1977;Zaidi et al, 1982a, b). Avian LH also consists of several components in the pituitary glands of chicken, Japanese quail, guinea fowl and duck (Hattori and Wakabayashi, 1979;Wakabayashi, 1980).…”
mentioning
confidence: 56%
“…Different pituitary FSH standards had been used for the validation of these biological assays. It had been previously demonstrated that pituitary and urinary gonadotropin preparations and standards exhibit different B/I ratios because of the marked heterogeneity of the gonadotropins (19,20,39). Comparing samples with standards of varying B/I ratios and bio-FSH activity makes the data difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…Serum factors may directly affect FSH action in target tissue. The molecular heterogeneity of the FSH molecules themselves may interfere or augment binding at target cell receptors leading to nonparallelism to the standards (19,20). Deglycosylated glycoproteins have been shown to be competitors of the intact hormone in receptor binding, but these isohormones have decreased potencies to stimulate steroidogenesis (21)(22)(23)(24)(25).…”
Section: In Vitro Bioassaysmentioning
confidence: 99%
“…This is because the intrinsic heterogeneity of these gonadotrophins, and the degree of purity of the urinaryderived products, has until now precluded their control by physicochemical methods or by in vitro assays. Thus highly purified preparations of FSH and LH have been shown to differ in their isoform compositions (Zaidi et al 1982a, b) and in their biological and immunological properties (Storring et al 1981(Storring et al , 1982. Bioassays used to control these gonadotrophin therapeutic products have been calibrated in terms of the third International Standard for Urinary FSH and LH (in ampoules coded 71/264; IS 71/264), which was established by the World Health Organization (WHO) in 1993 (WHO Expert Committee on Biological Standardization (ECBS) 1994).…”
Section: Introductionmentioning
confidence: 99%